Solidification of Fe19Cr2.9C2V alloy - Filipovic, Mirjana; Kamberovic, Zeljko; Korac, Marija (Journal of Mining and Metallurgy, Section B: Metallurgy, 2014)
The addition of 2% V affects the solidification process and changes the transformation characteristics of austenite in hypoeutectic white cast iron containing 19% Cr and 2.9% C. DTA analysis reveals that vanadium reduces the solidification temperature interval in tested alloy. The narrowing of the solidification temperature interval and the formation of vanadium carbides favours the appearance of a finer structure. Also, the phases volume fraction changes, i.e. the primary γ-phase fraction decreases and the amount of M7C3 carbide increases. Changes in conditions of solidification, as a result of adding vanadium to Fe-Cr-C white iron, influence the change in composition of austenite, which manifests itself in the form of different degrees of transformation of austenite.